Transforming agrifood systems in Zambia: What are the priorities and how much will it cost? - Chikolwa, Kabwe; Eber-Rose, Mali; Mwale, Lawrence; Picard, Francine; Scholtz, Louise; Siwale, Chilufya; Smaller, Carin; Mamun, Abdullah; Piñeiro, Valeria; Olivetti, Elsa B. (Shamba Centre for Food & Climate, 2025)
Zambia is not on track to achieve the United Nations Sustainable Development Goals (SDGs) by 2030. Its lack of progress is further exacerbated by the country’s maize-centric and rain-fed agriculture sector that is vulnerable to recurring drought cycles predicted to worsen with climate change. At the time of writing this report, Zambia once again is in the grip of a severe drought that destroyed close to half the country’s crops. To get back on track, it is critical to pursue policy pathways that favour synergies and limit the trade-offs between hunger, poverty, nutrition, and climate change. This report presents an evidence-based prioritization of effective interventions to operationalize Zambia’s Food Systems Transformation Pathways to end hunger, make diets healthier and more affordable, improve the productivity and incomes of small-scale producers, and mitigate and adapt to climate change.